Schema and deviation effects in remembering repeated unfamiliar stories. (1st June 2020) - Rubínová, Eva; Blank, Hartmut; Koppel, Jonathan; Ost, James
Abstract : In today's globalized world, we frequently encounter unfamiliar events that we may have difficulty comprehending – and in turn remembering – due to a lack of appropriate schemata. This research investigated schema effects in a situation where participants established a complex new schema for an unfamiliar type of story through exposure to four variations. We found that immediate recall increased across subsequent stories and that distortions occurred less frequently – participants built on the emerging schema and gradually established representations of parts of the story that were initially transformed. In recall with delays increasing up to 1 month, quantitative measures indicated forgetting while distortions increased. The second focus of this research was on content and order deviation effects on recall. The content deviation, in contrast with previous repeated‐event research, was not remembered well and was associated with lower recall; the order deviation had a similar (but expected) effect. We discuss discrepancies between results of this study and previous literature, which had focused on schemata for familiar events, in relation to stages of schema development: it seems that in unfamiliar repeated events, a complex new schema is in the early stages of formation, where the lack of attentional resources limits active processing of deviations.